Sistem Informasi Pariwisata Pantai Glory Melur Berbasis Web - Abdul Halim Husnul; Nurhatisyah Nurhatisyah; John Friadi (Jurnal Ilmu Siber dan Teknologi Digital, 2022)
After the Covid-19 pandemic that hit Indonesia, the government through the Ministry of Tourism and Creative Economy (Kemenparekraf) formulated several new policies to restore the tourism economy in Indonesia. The government also believes that this policy can attract foreign tourists to visit Indonesia, especially Bali, Batam and Bintan. Tourists can enjoy various tourist destinations in Batam. Glory Melur Beach is also one of the tourist attractions visited by many local and foreign tourists. Glory Melur Beach has various facilities that can be rented, but information regarding the rental of facilities is still limited. Purpose: For this reason, this study aims to create a web-based information system that can manage and disseminate information on Glory Melur beach tourism. Methodology: The system development method used is waterfall modeling. With this system, it is hoped that visitors can easily find out information about entrance ticket prices, rental rates for facilities and can find out information on the availability of halls at Glory Melur Beach because it can be accessed anywhere and anytime in any place that is connected to the internet. For this reason, in the future, Glory Melur beach management must always update the existing database with the latest tourism development information and complete this system according to technological developments by adding more complete features according to the needs of visitors. Results: The results of this study are to attract foreign and local tourists, the authors will create an information system on Glory Melur Beach. With this information system, it can make it easier for visitors to find information about the facilities and rental prices available at Glory Melur Beach. With this online Hall ordering system, it can make it easier for visitors and officers of Glory Melur Beach to easily order and manage the Hall, because it can be accessed anywhere and anytime in an internet-connected place.